ChemInform Abstract: Multicomponent Synthesis of Antibacterial Dihydropyridin and Dihydropyran Embelin Derivatives. Issue 52 (24th December 2013) - Pena, Rosalyn; Jimenez‐Alonso, Sandra; Feresin, Gabriela; Tapia, Alejandro; Mendez‐Alvarez, Sebastian; Machin, Felix; Ravelo, Angel G.; Estevez‐Braun, Ana
Abstract Coupling of embelin with aldehydes and the primary enaminones (III) provides a new, straightforward one‐pot approach to dihydropyridine derivatives of type (IV).